Cervical fusion cage computationally optimized with porous architected Titanium for minimized subsidence. (September 2018) - Moussa, Ahmed; Tanzer, Michael; Pasini, Damiano
Abstract: Anterior cervical discectomy with fusion is a common surgical treatment that can relieve patients suffering from cervical spondylosis. This surgery is most commonly performed with the use of a cervical cage. One serious complication of the fusion cages commercially available in the market is subsidence of the cage with loss of the normal alignment of the spine and recurrent pain. This work presents the proof-of-concept of a fusion cage made of a graded porous titanium with microarchitecture minimizing the risk of subsidence associated with fully-solid implants. The optimized properties of the porous implant are obtained through a scheme combining multiscale mechanics and density-based topology optimization. Asymptotic homogenization is used to capture the effective properties of the porous material, which uses a tetrahedron based cell as building block. The stress levels and normal strains obtained under various loading conditions on the C7 superior surface of the vertebrae are used as indicators of subsidence. The results suggest a reduced risk of subsidence for the optimized implant versus the fully-solid implant. Under the most severe condition of combined loading, a collective improvement of the average von Mises stress up to 14% can be observed on the posterior, left, and right lateral regions of the C7 superior surface. Similarly, for the average normal strain, the optimized cage exhibits a more favourable distribution with a top gain of 21.7% at given locations. Graphical abstract: fx1 Highlights: Architected porous cage reduces elastic properties mismatch with adjacent vertebrae. Optimized elasticity gradients provide reduced risk of cage subsidence. Critical stress and strain location are dependent on the loading case. Combined multiaxial loadings lead to the highest probability of subsidence.